Statistical Adiabatic Channel Model Calculations of the Reaction of H Atoms and FO Radicals on Ab Initio Potential Energy Surfaces - Cobos, Carlos Jorge (2000)
The statistical adiabatic channel model has been used to calculate rate coefficients for the reaction between H atoms and FO radicals on potential energy surfaces based on density functional theory and ab initio calculations between 200 and 1000 K. The rate coefficient calculated at 300 K with the ab initio potential is in good agreement with a recently reported experimental value.